RANCANG BANGUN CHARGER OTOMATIS AGV BERBASIS NODEMCU ESP 32 - Dimas Arditya Akbar (Politeknik Harapan Bersama Tegal, 2022)
Abstract AGV (Automated guided vehicle) is a vehicle that serves to transport goods, AGV (Automated guided vehicle) only requires a small human role but behind these advantages there are disadvantages, namely the relatively expensive price compared to using a forklift or the like and using a power source from batteries which has a small capacity so it must be charged regularly. However, this AGV (Automated guided vehicle) charger is still operated manually by humans. This research focuses on innovations in automatic charger stations that can be controlled remotely. The advantage is to minimize the occurrence of human errors that result in battery damage. In this study, the charger station uses a microcontroller nodeMCU ESP 32 and is controlled remotely using an ESP 32 wifi module whose function is to connect and disconnect this charger if an error occurs during charging, this charger uses a limit switch that functions to become a switch, namely when the limit switch, for sensors temperature using the DHT11 sensor to determine the temperature of the AGV battery if the temperature exceeds the specified then the charger will automatically break, to detect current and voltage use the Ina 219 sensor to display results using the LCD 16x2 and for remote control with the blynk app. Keywords : NodeMCU ESP 32, Blynk Application, AGV, IOT